2018
DOI: 10.1002/hbm.23978
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disadvantage and altered corticostriatal circuitry in urban youth

Abstract: Socioeconomic disadvantage (SED) experienced in early life is linked to a range of risk behaviors and diseases. Neuroimaging research indicates that this association is mediated by functional changes in corticostriatal reward systems that modulate goal-directed behavior, reward evaluation, and affective processing. Existing research has focused largely on adults and within-household measures as an index of SED, despite evidence that broader community-level SED (e.g., neighborhood poverty levels) has significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 122 publications
0
41
0
Order By: Relevance
“…Electroencephalographic (EEG) studies have found evidence of a maturational lag in the prefrontal cortex (Otero 1997) in addition to left-frontal hypoactivity (Tomarken et al 2004) in lower SES preschool children and adolescents, respectively; these findings correspond to the findings of behavioral studies examining language and attention differences between groups (Hackman and Farah 2009). A review of fMRI studies suggest decreased functional specialization in language regions for low-SES kindergartners (Raizada et al 2008), less mature frontal gamma power in low-SES children (Tomalski et al 2013), and decreased functional connectivity at resting-state in low-SES children and adults (Sripada et al 2014;Barch et al 2016;Marshall et al 2018), suggesting a comparative delay in functional brain development (Tooley et al 2018). In agreement with these functional studies, our findings of asymmetric cortical correlates of SES disparities, with reduced thickness for participants with lower SES in the left-hemispheric language-related regions with concurrent decrease in vocabulary and reading scores also suggest delayed cortical development with behavioural consequences for participants with lower SES.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalographic (EEG) studies have found evidence of a maturational lag in the prefrontal cortex (Otero 1997) in addition to left-frontal hypoactivity (Tomarken et al 2004) in lower SES preschool children and adolescents, respectively; these findings correspond to the findings of behavioral studies examining language and attention differences between groups (Hackman and Farah 2009). A review of fMRI studies suggest decreased functional specialization in language regions for low-SES kindergartners (Raizada et al 2008), less mature frontal gamma power in low-SES children (Tomalski et al 2013), and decreased functional connectivity at resting-state in low-SES children and adults (Sripada et al 2014;Barch et al 2016;Marshall et al 2018), suggesting a comparative delay in functional brain development (Tooley et al 2018). In agreement with these functional studies, our findings of asymmetric cortical correlates of SES disparities, with reduced thickness for participants with lower SES in the left-hemispheric language-related regions with concurrent decrease in vocabulary and reading scores also suggest delayed cortical development with behavioural consequences for participants with lower SES.…”
Section: Discussionmentioning
confidence: 99%
“…There is little doubt that higher levels of chronic, low-grade stress are experienced in South Los Angeles' disadvantaged neighborhoods compared to green (rich in both vegetation and money), billboard-free neighborhoods, like Bel Air; the emerging research indicates that neighborhood-level deprivation-low socioeconomic position and the entire package of grey space-is manifesting as inflammation, oxidative stress, disturbances to the gut microbiome (dysbiosis), alterations in the brain reward system, and metabolic dysregulation [169][170][171][172][173][174]. Research shows that baseline psychological stress compounds the inflammatory and detrimental circulatory responses to a single fast-food-style meal [175,176].…”
Section: The Mcdonald's ® Meal Storymentioning
confidence: 99%
“…As in the case of psychology and genomics, neuroscience research is largely based on data of individuals from WEIRD societies (Falk et al 2013), despite a plethora of studies showing that brain development is affected by socioeconomic status, early life stress, or cultural differences (Hackman et al 2010;Marshall et al 2018;Chan et al 2018;Duval et al 2017;Liddell and Jobson 2016). Indeed, within or across household socio-economic variables during childhood, such as family income, parental education (Ellwood-Lowe et al 2018;Weissman et al 2018) or neighbourhood poverty levels (Marshall et al 2018), can be traced on trajectories of brain development, and result in differences in brain structure (Ellwood-Lowe et al 2018) and cognitive functions (Hackman and Farah 2018), or gene expression (Parker et al 2017). Differences in brain networks according to socio-economic status are also evident during adolescence (Weissman et al 2018) and adulthood (Chan et al 2018).…”
Section: Sharing Neurobiological Datamentioning
confidence: 99%